The synthesis and evaluation of anti-acetylcholinesterase activity of some 4(3H)-quinazolinone derivatives bearing substituted 1,3,4- thiadiazole - Uraz, Mine; Karakuş, Sevgi; Mohsen, Usama Abu; Kaplancıklı, Zafer Asım; Rollas, Sevim (My University, 2017)
In the present study, a series of 4(3H)-quinazolinone derivatives (5a-f) were synthesized through the cylization reaction of substituted 1,3,4-thiadiazoles containing an aromatic primary amin and anthranilic acid in the presence of acetic anhydride and acetic acid. The structures of the synthesized compounds were confirmed by elemental analysis, IR, 1 H-NMR and mass spectroscopic (5b and 5f) methods. Each derivative was evaluated for its ability to inhibit acetylcholinesterase (AChE) using a modification of Ellman’s spectrophotometric method. Compounds 2-methyl-3-{4-[5-(ethylamino)-1,3,4-thiadiazol- 2-yl]phenyl}quinazolin-4(3H)-one (5b) and 2-methyl-3-{4-[5- (cyclohexylamino)-1,3,4-thiadiazol-2-yl]phenyl}quinazolin- 4(3H)-one (5d) can be identified as promising anticholinesterase agents due to their inhibitory effect when compared with donepezil as a reference drug.
Keywords: 4(3H)-Quinazolinone, 1,3,4-thiadiazole, antiacetylcholinesterase activity.